Effect of incident angle of P-wave on seismic response of underground cavern. (May 2023) - Han, Guohui; Su, Chao; Wang, Wenjun; Yu, Hui
Abstract: This study investigates the effect of the P-wave incident angle on the seismic response of a rock mass surrounding an underground cavern in a hydropower station. Based on the viscoelastic artificial boundary theory and analysis of the incident and reflected states of P-waves at any angle in a semi-infinite medium, a comprehensive and effective analytical model of the oblique incidence of seismic waves is established. In the analysis model, conversion of the obliquely incident seismic wave time history and equivalent nodal force was implemented using the commercial software ABAQUS; the reliability of the method was verified using a numerical case. Using this method, the seismic responses of the rock mass surrounding an underground cavern under the action of incident P-waves at different angles were studied in terms of stress, displacement, and plastic damage. The results showed a significant effect of the oblique incidence of seismic waves on the dynamic response of the underground cavern.